Kelimpahan Populasi dan Persentase Serangan Lalat Buah (Bactrocera Spp.) (Diptera: Tephritidae) pada Tanaman Mentimun (Cucumis Sativus L.) di Beberapa Kabupaten Provinsi Bali - Agustini, Ni Wayan Suryati; Sunari, A.A. Ayu Agung Sri; Yuliadhi, Ketut Ayu (Journal of Agricultural Science and Biotechnology; Vol 8 No 1 (2019), 2019)
The research aims to determine the population abundance and the damage percentage of fruit fly. The study was conducted in Tabanan Regency villages of Candikuning and Baturiti, Badung Regency villages of Belok-sidan and Kapal and Klungkung Regency villages of Gelgel which took place from February to April 2019. Fruit sampling was done purposively by taking fruits that showed symptoms of fruit fly attacks which were then maintained in the Integrated Pest and Disease laboratory of the Agriculture Faculty, Udayana University. The identification results show that there were 2 species of fruit flies that attacked the cucumber, namely Bactrocera cucurbitae and Bactrocera calumniata. The population abundance of B. cucurbitae species in Tabanan Regency (69.7%), Badung Regency (71.2%) and Klungkung Regency (74%), while the population abundance of B. calumniata species in Tabanan Regency (30.2%), Badung Regency (28.8%) and Klungkung Regency (26%). The percentage of damage were in Tabanan Regency (22.9%), Badung Regency (22%) and Klungkung Regency (27.3%).